A randomized, open-label, multi-center, active-controlled phase II study comparing abiraterone acetate tablets (II), an improved formulation, versus originator abiraterone acetate in patients with metastatic castration-resistant prostate cancer - Xiaolin Lu; Tao Dai; Xue Chen; Bin Wu; Hui Chen; Jitao Wu; Dexin Yu; Huixin Ge; Jian Li; Houbao Huang; Tiwu Fan; Linzhong Cheng; et al. (BMC Medicine)
Abstract Background Abiraterone is a 17α-hydroxylase/C17-20 lyase inhibitor used for the treatment of metastatic castration-resistant prostate cancer (CRPC). This multi-center, randomized, open-label, active-controlled phase II study compared the pharmacodynamics (PD), pharmacokinetics (PK), and safety of abiraterone acetate tablets (II) (AAT[II]), a new formulation of abiraterone acetate, and ZYTIGA®, the originator abiraterone acetate (OAA), in patients with metastatic CRPC. Methods Patients were randomized 1:1 to receive 300 mg AAT(II) daily plus 5 mg prednisone twice daily or 1000 mg OAA daily plus 5 mg prednisone twice daily for 84 days. The primary endpoint was the serum testosterone level (rounded-up) on Day 9 and/or Day 10. Absolute testosterone concentration, prostate-specific antigen (PSA) concentration, steady-state PK of abiraterone, and safety were also evaluated. Results Sixty-nine patients were enrolled in the study, with 35 assigned to AAT(II) and 34 to OAA. The least squares (LS) mean (standard error) of serum testosterone concentration (rounded-up) on Day 9 and/or Day 10 were 1.075 (0.034) and 1.000 (0.034) in the AAT(II) and OAA groups, respectively. The geometric mean ratio (AAT[II] vs. OAA) was 1.053 (90% confidence interval [CI], 0.998 to 1.110) and the LS mean difference was 0.075 (95% CI, -0.021 to 0.171). The 90% CI fell within the 80.0% to 125.0% equivalence limits, suggesting equivalent PD effect of the two formulations. AAT(II) also exhibited high testosterone inhibition rate (> 90% at all visits) and PSA-50 rate (> 65% on Days 56 and 84), which were comparable to that of OAA. AAT(II) also demonstrated an improved safety profile with lower incidence of adverse events compared to OAA. Conclusions AAT(II) at 300 mg plus prednisone demonstrated equivalent PD as OAA at 1000 mg plus prednisone in reducing serum testosterone on Day 9 and/or Day 10, and the effect was maintained up to the end of the study. Compared to OAA, AAT(II) was given at a much lower dosage and was not affected by food consumption. AAT(II) was well tolerated, and no new safety issues were found. Trial registration ClinicalTrials.gov, NCT04862091.